Análisis de aplicaciones móviles basadas en Realidad Aumentada para el aprendizaje de la asignatura de Ciencias Naturales para los estudiantes Educación Básica Superior. - Amboya Caranqui, Betty Marlene (2024)
The main objective of this research study was to focus on mobile applications based on augmented reality that are virtual tools to support the teaching and learning of students by transforming an educational experience, facilitating a deeper and more practical understanding of the contents. The objective was to analyze mobile applications based on augmented reality for learning the subject of Natural Sciences for students of Higher Basic Education in order to know the applications suitable for the learning process. The data collection of the different applications was based on a quantitative approach, documentary type, with a non-experimental design and descriptive scope. Three augmented reality tools were selected from a total of 15 applications where the technical and educational data sheet was used, reaching the conclusion that the tools Quivervision, Assembler Edu and Object Viewer are suitable for teaching and learning as they have the necessary functions for the study. The applications were also categorized according to the current curriculum of the Ministry of Education.